answersLogoWhite

0


Best Answer

Where is y in the first equation, you put its equivalent (=) -3x + 11

The first equation is then transformed into: 3x + 2*(-3x + 11) = 7.

Then you get: 3x + (-6x) + 2*11 = 7 <=> -3x + 22 = 7 <=> 22 - 7 = 3x <=> 3x = 15 <=> x = 15/3 <=> x = 5. Then you substitute the x in the second equation by its equivalent so,

(x = 5)

y = -3*x + 11 <=> y = -3*5 + 11 <=> y = -15 + 11 <=> y = -4.

x = 5. y = -4.

User Avatar

Wiki User

13y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: How to Solve the system using substitution 3x plus 2y equals 7 y equals negative 3x plus 11?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

Use the substitution method to solve the system of equations Choose the correct ordered pair 2x plus 3y equals 13 x equals 2?

(2,3)


How would use solve the system of equation x plus 3y equals 23 by using substitution?

You'd need another equation to sub in


What are three ways to solve a system?

elimination, substitution and graphing


To solve a three variable system of equations you can use a combination of the elimination and substitution methods?

True. To solve a three variable system of equations you can use a combination of the elimination and substitution methods.


Use the substitution method to solve the system of equations Enter your answer as an ordered pair?

Use the substitution method to solve the system of equations. Enter your answer as an ordered pair.y = 2x + 5 x = 1


What 4x y14 and 2x y8 solve using substitution?

You cant solve it unless it is an equation. To be an equation it must have an equals sign.


Solve the equation by substitution method x-y equals 5?

x+y=5


Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24?

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4


How do use substitution when solving system of equations?

You use substitution when you can solve for one variable in terms of the others. By substituting, you remove one variable from the equation, which can then be solved. Once you solve for one variable, you can use substitution to find the other.


Solve the system of equations using the elimination method negative x plus y equals negative 3 and 3x plus 2y equals 9?

By elimination: x = 3 and y = 0


What is indicated by the occurrence of a false statement such as 0 equals 1 when you solve a system of two linear equations in two variables using substitution?

In that instance, it means that the lines never touch.


Solve the system by substitution x= 5 - y x-y=3?

2